Computation of the glandular radiation dose in digital tomosynthesis of the breast - Sechopoulos, Ioannis (Med Phys, 2007)
Tomosynthesis of the breast is currently a topic of intense interest as a logical next step in the evolution of digital mammography. This study reports on the computation of glandular radiation dose in digital tomosynthesis of the breast. Previously, glandular dose estimations in tomosynthesis have been performed using data from studies of radiation dose in conventional planar mammography. This study evaluates, using Monte Carlo methods, the normalized glandular dose (D(g)N) to the breast during a tomosynthesis study, and characterizes its dependence on breast size, tissue composition, and x-ray spectrum. The conditions during digital tomosynthesis imaging of the breast were simulated using a computer program based on the Geant4 toolkit. With the use of simulated breasts of varying size, thickness and tissue composition, the D(g)N to the breast tissue was computed for varying x-ray spectra and tomosynthesis projection angle. Tomosynthesis projections centered about both the cranio-caudal (CC) and medio-lateral oblique (MLO) views were simulated. For each projection angle, the ratio of the glandular dose for that projection to the glandular dose for the zero degree projection was computed. This ratio was denoted the relative glandular dose (RGD) coefficient, and its variation under different imaging parameters was analyzed. Within mammographic energies, the RGD was found to have a weak dependence on glandular fraction and x-ray spectrum for both views. A substantial dependence on breast size and thickness was found for the MLO view, and to a lesser extent for the CC view. Although RGD values deviate substantially from unity as a function of projection angle, the RGD averaged over all projections in a complete tomosynthesis study varies from 0.91 to 1.01. The RGD results were fit to mathematical functions and the resulting equations are provided.